LEADERSHIP STRATEGIES IN FOSTERING NATIONAL INSIGHT FROM THE PERSPECTIVE OF MULTICULTURAL ISLAMIC RELIGIOUS EDUCATION IN KAPUAS HULU REGENCY - Susintoi, Susintoi; Kartono, Kartono; Maskuri, Maskuri; Ghony, M. Djunaidi (UIN Mataram dan Asosiasi Sosiologi Agama Indonesia (ASAGI), 2025)
The Kapuas Hulu Regency is home to a diverse array of ethnicities and cultures, requiring a leadership approach that can strengthen national values and interfaith tolerance. This study aims to examine leadership strategies for nurturing national insight in Kapuas Hulu, from the perspective of multicultural Islamic Religious Education. This research uses a qualitative method, with data collection through observation, interviews, and documentation, and data analysis is conducted through data condensation, data display, and drawing conclusions. The research findings indicate that leaders in Kapuas Hulu implement an inclusive approach in Islamic religious education, which not only emphasizes religious values but also encourages respect for cultural and ethnic differences. The leadership strategies applied in Kapuas Hulu include: a) Education and Socialization of Pancasila Values, b) Maintaining Diversity and Tolerance Among Ethnic Groups, Religions, and Races, and c) Strengthening National Identity through Culture and Traditions. These strategies reflect the efforts of leaders in Kapuas Hulu to nurture a sense of nationalism amid diversity in a pluralistic society. Additionally, leadership strategies should be directed toward the education sector as an effort to cultivate national values among the younger generation, such as: a) Raising Multicultural Awareness Among Students, b) Integrating Character Education into the Curriculum, andc) Creating a Tolerant and Inclusive Educational Environment. These strategies are being applied in the educational sector in Kapuas Hulu. However, leaders in Kapuas Hulu face challenges in practicing these strategies in everyday life, such as the high level of diversity and stereotypes.